RELIGIOUS MODERATION-BASED CURRICULUM FOR URBAN MUSLIMS: A STUDY IN ISLAMIC UNIVERSITY OF INDONESIA ISLAMIC BOARDING SCHOOL - Suparta, Suparta (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
Islamic boarding schools are educational institutions developed to prevent radicalism through peaceful, open, and moderate education patterns. The role encounters new challenges marked by the formation of urban Muslims and the potential vulnerability to radical ideologies facilitated by digital media exposure. In this context, the curriculum should be updated to accommodate urban Muslim culture while preventing radicalism. Islamic University of Indonesia (UII) Islamic Boarding School has a complex curriculum and material content. The primary effort of this school in facing the modern era is by applying the principle of religious moderation in the learning curriculum. Therefore, this qualitative study aimed to examine the curriculum used by UII Islamic Boarding School to strengthen the perspective of religious moderation for students. Primary data consisted of leaders and alumni of UII Islamic Boarding School Yogyakarta. Meanwhile, secondary data comprised written sources from journal articles, books, theses, and dissertations that discussed Islamic boarding schools. Data were also collected and analyzed using interviews and phenomenological techniques, respectively. The results showed that the curriculum material was oriented to form the character of moderate students in the modern era. This could be seen from the students' profile graduates as agents of peace among religious communities with the capacity of faith stability, intellectual and reasoning abilities, da’wah (proselytizing) ability, and proficiency in foreign languages. In the UII Islamic Boarding School, the curriculum material's contents were dominated by a model based on religious moderation seen in the syllabus or subject. Therefore, the thoughts produced by the alumni became moderate, and this was appropriate to the vision and mission of UII, which was to produce Muslim scientists who were rahmatalilalamiin.